REFLEKSI FILOSOFIS TERHADAP BUNYI KOSMIK DAN MUSIK DALAM MEWUJUDKAN HARMONI KEHIDUPAN - Prasanthy Devi Maheswari; Jyothi Devi Krishnanandayani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study is a philosophical reflection on the meaning of cosmic sound (nāda brahman) and music in the Hindu philosophical tradition as a contemplative and transformative medium for realizing harmony in life. This research aims to re-explore the metaphysical, aesthetic, and practical dimensions of musical experience as understood in classical Hindu texts. This research aims to show that sound and music, when understood philosophically, can be a medium for the formation of harmony in life and the transformation of consciousness towards a whole and integral cosmic consciousness. In the Nāṭyaśāstra, as a fundamental text of classical Indian art, Bharata Muni positions music (gāndharva) as a direct manifestation of the cosmic principle, namely rotating universal rhythms through the medium of aesthetics. Art, in this framework, is understood as an expression of cosmic movement that functions to awaken consciousness through the experience of feeling. Through a hermeneutic and phenomenological approach, this study reveals the integration of metaphysical, aesthetic, and practical dimensions in human musical experience. The results of the reflection show that aesthetic experience, as formulated in the Nāṭyaśāstra, has a transformative power: it arouses emotions, harmonizes psychic structures, and opens the way to higher consciousness. Thus, cosmic sound and music not only represent harmony, but become a medium for self-realization—as a process of unification of the microcosm (human) with the macrocosm (universe), which states that all reality essentially vibrates in one universal cosmic rhythm.